2003
DOI: 10.1046/j.1360-2276.2003.01120.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyparasitism with Schistosoma haematobium and soil‐transmitted helminth infections among school children in Loum, Cameroon

Abstract: SummaryPrevalence and abundance of Schistosoma haematobium and soil-transmitted helminths (STH) were assessed among a total of 1600 pupils (urine, n ¼ 1190; faecal samples, n ¼ 1454) attending five schools in Loum, Littoral Province, Cameroon, with the specific aim of assessing the extent of polyparasitism and the extent to which infections were focused in particular subsets of the study group. Prevalence of S. haematobium was 62.8% with an abundance (arithmetic mean of egg counts) of 54 eggs/10 ml urine. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
72
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 30 publications
11
72
1
Order By: Relevance
“…Our data underscore that multiparasitism is very common in Lao PDR and these findings support observations from neighbouring countries such as Vietnam [25][26][27] and from other parts of the developing world. 21,22,[28][29][30] Hence, our results and those from other groups who worked in Lao PDR 7,8 call for concerted action to remedy the issue of multiparasitism. Of particular public health relevance are our results in relation to the diversity of trematodes identified.…”
Section: Discussionsupporting
confidence: 53%
“…Our data underscore that multiparasitism is very common in Lao PDR and these findings support observations from neighbouring countries such as Vietnam [25][26][27] and from other parts of the developing world. 21,22,[28][29][30] Hence, our results and those from other groups who worked in Lao PDR 7,8 call for concerted action to remedy the issue of multiparasitism. Of particular public health relevance are our results in relation to the diversity of trematodes identified.…”
Section: Discussionsupporting
confidence: 53%
“…Finally, an increasing number of studies of helminth epidemiology have shown that it is common for individuals to be infected with more than one species of helminth (21,(58)(59)(60)(61)(62)(63). There is also evidence suggesting synergism and antagonism in concurrent intestinal nematode and schistosome infections (62-64) as well as filarial nematode infection and soil-transmitted helminth infections (65).…”
Section: Epidemiology Of Helminth Infectionsmentioning
confidence: 99%
“…There is also evidence suggesting synergism and antagonism in concurrent intestinal nematode and schistosome infections (62-64) as well as filarial nematode infection and soil-transmitted helminth infections (65). A number of epidemiological studies have indicated that individuals infected with multiple species of helminth often harbor heavier infections than individuals infected with a single helminth species (58)(59)(60)(61). An important consequence of simultaneous infection with the parasites that cause hookworm, schistosomiasis, and malaria is severe anemia (21,66).…”
Section: Epidemiology Of Helminth Infectionsmentioning
confidence: 99%
“…In Cameroon, IPIs are recognized by the Ministry of Public Health to be an important public health problem ranking second to malaria [7]. There has been periodic de-worming in most endemic areas in the country, but studies suggest that there is a high rate of re-infection [8].…”
Section: Introductionmentioning
confidence: 99%